Recording nerve signals in canine sciatic nerves with a flexible penetrating microelectrode array. (14th June 2017) - Byun, Donghak; Cho, Sung-Joon; Lee, Byeong Han; Min, Joongkee; Lee, Jong-Hyun; Kim, Sohee
Abstract: Objective . Previously, we presented the fabrication and characterization of a flexible penetrating microelectrode array (FPMA) as a neural interface device. In the present study, we aim to prove the feasibility of the developed FPMA as a chronic intrafascicular recording tool for peripheral applications. Approach . For recording from the peripheral nerves of medium-sized animals, the FPMA was integrated with an interconnection cable and other parts that were designed to fit canine sciatic nerves. The uniformity of tip exposure and in vitro electrochemical properties of the electrodes were characterized. The capability of the device to acquire in vivo electrophysiological signals was evaluated by implanting the FPMA assembly in canine sciatic nerves acutely as well as chronically for 4 weeks. We also examined the histology of implanted tissues to evaluate the damage caused by the device. Main results . Throughout recording sessions, we observed successful multi-channel recordings (up to 73% of viable electrode channels) of evoked afferent and spontaneous nerve unit spikes with high signal quality (SNR > 4.9). Also, minor influences of the device implantation on the morphology of nerve tissues were found. Significance . The presented results demonstrate the viability of the developed FPMA device in the peripheral nerves of medium-sized animals, thereby bringing us a step closer to human applications. Furthermore, the obtained data provide a driving force toward a further study for device improvements to be used as a bidirectional neural interface in humans.